PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN ATLET BOLA VOLI PUTRI CLUB GESIMPO KABUPATEN PASAMAN BARAT - Yulia Dewi Syaputri; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to find out the Effect of Interval Training Training on the Endurance of Women's Volleyball Athletes Club Gesimpo In Pasaman Barat. This research was conducted at Club Gesimpo Volleyball Court, Aua Kuniang, Pasaman ,Pasaman barat . Held in May-July 2021. The study used the one-group preetest-posttest design method. The population in this study was 8 people consisting of a group of women. Sampling in this study uses the total sampling technique where the entire population is a sample consisting of 8 people. This research instrument uses bleep-test, analytical techniques using the t-test. Based on uij-t produce Thitung = 2,371 while Ttabel obtained by 1,895, so Thitung > Ttabel, at the alpha level of 0.05. It can be concluded that there is an effect of interval training training on the endurance of women's volleyball athletes club gesimpo in pasaman barat.Key Words: Interval Training, Vo2max Endurance, Volleyball